Genetic and phenotypic assessment of the antimicrobial activity of three potential probiotic lactobacilli against human enteropathogenic bacteria - Kiousi, Despoina Eugenia; Efstathiou, Christos; Tzampazlis, Vasilis; Plessas, Stavros; Panopoulou, Maria; Koffa, Maria; Galanis, Alex (Frontiers in Cellular and Infection Microbiology, 2023)
Lactobacilli are avid producers of antimicrobial compounds responsible for their adaptation and survival in microbe-rich matrices. The bactericidal or bacteriostatic ability of lactic acid bacteria (LAB) can be exploited for the identification of novel antimicrobial compounds to be incorporated in functional foodstuffs or pharmaceutical supplements. In this study, the antimicrobial and antibiofilm properties of Lactiplantibacillus pentosus L33, Lactiplantibacillus plantarum L125 and Lacticaseibacillus paracasei SP5, previously isolated form fermented products, were examined, against clinical isolates of Staphylococcus aureus, Salmonella enterica subsp. enterica serovar Enteritidis and Escherichia coli. Specifically, the ability of viable cells to inhibit pathogen colonization on HT-29 cell monolayers, as well as their co-aggregation capacity were examined. Additionally, the antimicrobial activity of cell-free culture supernatants (CFCS) was determined against planktonic cells and biofilms, using microbiological assays, confocal microscopy, and gene expression analysis of biofilm formation-related genes. The efficiency of the potentially probiotic bacteria to elicit antimicrobial effects presented a strain- and pathogen-specific pattern, while greater inhibition of viability and biofilm formation was recorded after co-incubation of S. enterica with the CFCS of Lc. paracasei SP5. Furthermore, in vitro analysis was supplemented with in silico prediction of bacteriocin clusters and of other loci involved in antimicrobial activity. Predictions based on sequence revealed the ability of strains to produce single or two-peptide Class II bacteriocins, presenting sequence and structural conservation with functional bacteriocins. Future studies, utilizing multi-omic approaches, will focus on the structural and functional characterization of molecules involved in the recorded phenotypes.